1971
DOI: 10.1104/pp.47.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Chilling Injury to Corn Seedlings

Abstract: Seedlings of corn (Zea mays) were tested for recovery from chilling injury incurred at 0.3 ± 0.3 C. At 0.3 C visual leaf injury appeared in 36 hours, whereas stem and root injuries appeared later. Appearance of leaf injury was preceded by a rise in 02 uptake and a lessened effect of 2,4-dinitrophenol on 03 uptake by leaf segments and was accompanied by increased ion leakage from the leaves. These effects were Temperatures that cause chilling injury vary with species and can be as high as 12.5 C (14). The low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 13 publications
3
32
1
Order By: Relevance
“…Chilling sensitivity has also been attributed to critical changes in membrane fluidity (Lyons et al, 1964;Lyons and Raison, 1970). Any phase changes in the inner mitochondrial membrane would have drastic effects on the orientation of the respiratory chain components with a concomitant reduction of electron flow through the Cyt chain (Creencia and Bramlage, 1971). These data support the hypothesis that the ability of the tissue to recover from these damaging temperature regimes depends on restoring electron flow to the normal Cyt pathway during recovery from chilling stress, which is evident from our recovery data.…”
Section: Chilling Lnhibits Cyt Pathway Of Electron Transportsupporting
confidence: 79%
“…Chilling sensitivity has also been attributed to critical changes in membrane fluidity (Lyons et al, 1964;Lyons and Raison, 1970). Any phase changes in the inner mitochondrial membrane would have drastic effects on the orientation of the respiratory chain components with a concomitant reduction of electron flow through the Cyt chain (Creencia and Bramlage, 1971). These data support the hypothesis that the ability of the tissue to recover from these damaging temperature regimes depends on restoring electron flow to the normal Cyt pathway during recovery from chilling stress, which is evident from our recovery data.…”
Section: Chilling Lnhibits Cyt Pathway Of Electron Transportsupporting
confidence: 79%
“…The increase in rate below 10 C was considerably greater for the L. hirsutum altitude variants (Fig. 4b), especially when compared to [3 H]leucine leakage from the same material (Fig. 4a).…”
mentioning
confidence: 91%
“…Liebermann et aL (7) found 5 times as much potassium leakage from sweet potato roots after 10 weeks storage at chilling temperatures. There was also enhanced leakage of electrolytes from leaf tissue (3,11,19) and fruit tissue (16) at chilling temperatures. The results of Tatsumi and Murata (16) showed that fruit pitting, a symptom of chilling injury, was visible after 5 days whereas leakage did not increase until the 7th day.…”
mentioning
confidence: 99%
“…For example, Creencia and Bramlage (2) showed that although corn seedlings held for 36 h at 0.3°C were undamaged when returned to ambient temperatures, those held for 48 h or more were irreversibly damaged.…”
mentioning
confidence: 99%